Using video docuseries to explore male professional football head coaches` well-being experiences throughout a season - Higham, A. J.; Rumbold, J. L.; Newman, J. A.; Stone, K. A. (Psychology of Sport and Exercise, 2023)
Football coaches have disclosed how their work environment is unpredictable and demanding, comprising a multitude of stressors which can impede well-being. Additionally, the masculine culture within football often promotes suppression of voice, causing internalisation of thoughts and isolation. Due to professional football head coaches being a seldom-heard group, little is known about how they experience well-being within their given context (i.e., ecological niche). The present study utilised football docuseries and a bioecological framework to explore how four male professional head coaches experienced well-being whilst working in one of the top European football leagues (Premier League, La Liga). Four docuseries were sampled and resulted in the analysis of 31 episodes (Mduration = 46.6 min, SD = 4.5 min). The study implemented an adapted interpretative phenomenological analysis approach to illuminate convergences and divergences in contextual accounts. These accounts resulted in five group experiential themes: `I belong to the game`; `he belongs to the game`; `you need the right people around you`; `it`s difficult to describe the manager without describing the person`; and `people are trying to stab you`. The findings indicate that football coaches may experience identity conflicts and become deeply absorbed in their work. This impacts not only their well-being but also their family`s, who they often turn to for social support. Consequently, by unveiling nuanced challenges to coaches` well-being, organisations may be better informed to offer more aligned and bespoke well-being support systems.